Pengembangan Model Latihan Servis Atas Bola Voli: Modifikasi Berbasis Permainan Pada Siswa Ektrakurikuler - Kurniawan, Septa; Melianty, Selvi; Endrawan, I Bagus; Kesumawati, Selvi Atesya; Alfani, Rendi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Efforts to optimize the movement of basic volleyball technical skills are an obligation that must be done by a coach, especially for amateur athletes in order to prepare for the next golden generation. The purpose of this study is to develop a model of volleyball service training for game-based students in junior high school extracurricular activities in Plakat Tinggi District. The development of a volleyball service training model in junior high school extracurricular activities in Plakat Tinggi District based on games was carried out using the stages of development research according to Brog & Gall. The validity criteria of the volleyball service training model were evaluated by four experts who are volleyball learning experts, coaches, movers and escul experts. The small group trial was carried out at SMP Negeri 4 Plakat Tinggi with a total of 26 students. The results of a large-scale trial of the volleyball service training model for game-based students were 92% which were included in the good/decent category. Based on the results of small-scale and large-scale trials, data was generated that showed that the trial was in the good/feasible category. It can be seen from the results of a small-scale trial with a percentage of 90% valid with revision and a large-scale trial with a percentage of 92% valid without revision. These results refer to the assessment guidelines that have been determined. The implication of this research lies in a training product that can be disseminated by coaches or teachers in improving the service of volleyball, especially in amateur class athletes.